Mode of Action of Two Streptococcus faecium Bacteriocins - Krämer, J. (1975)
The mechanism of action of enterocins E1A and E1B, bacteriocins produced by Streptococcus faecium E1, was studied. The enterocins killed susceptible cells rapidly, but cell lysis does not appear to be involved directly. Susceptible cells could be rescued from the lethal damage by trypsin treatment only within 2 to 3 min after addition of enterocin E1A. Enterocins E1A and E1B inhibited protein synthesis and drastically reduced biosynthesis of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) but did not cause degradation of DNA or RNA. Enterocin E1A strongly inhibited the accumulation of isoleucine and caused rapid exit of previously accumulated isoleucine.